Choline transporter-like1 (CHER1) is crucial for plasmodesmata maturation in Arabidopsis thaliana - Kraner, Max; Link, Katrin; Melzer, Michael; Ekici, Arif Bülent; Uebe, Steffen; Tarazona, Pablo; Feussner, Ivo; Hofmann, Jörg; Sonnewald, Uwe (Plant Journal, 2016)
Plasmodesmata (PD) are microscopic pores connecting plant cells and enable cell-to-cell transport. Currently, little is known about the molecular mechanisms regulating PD formation and development. To uncover components of PD development we made use of the 17 kDa movement protein (MP17) encoded by the Potato leafroll virus (PLRV). The protein is required for cell-to-cell movement of the virus and localises to complex PD. Forward genetic screening for Arabidopsis mutants with altered PD-binding of MP17 revealed several mutant lines, while molecular genetics, biochemical and microscopic studies allowed further characterisation. Map-based cloning of one mutant revealed a point mutation in the choline transporter-like 1 (CHER1) protein, changing glycine(247) into glutamate. Mutation in CHER1 resulted in a starch excess phenotype and stunted growth. Ultrastructure analysis of shoot apical meristems, developing and fully developed leaves showed reduced PD numbers and the absence of complex PD in fully developed leaves. This indicates that cher1 mutants are impaired in PD formation and development. Global lipid profiling revealed only slight modifications in the overall lipid composition, however, altered composition of PD-associated lipids cannot be ruled out. Thus, cher1 is devoid of complex PD in developed leaves and provides insights into the formation of complex PD at the molecular level. This article is protected by copyright. All rights reserved.
EVALuna2:9344